2012
DOI: 10.1371/journal.pone.0052398
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Imaging Provides Spatiotemporal Information on Disease Progression and Response to Therapy in a Murine Model of Multiple Myeloma

Abstract: BackgroundMultiple myeloma (MM) is a B-cell malignancy, where malignant plasma cells clonally expand in the bone marrow of older people, causing significant morbidity and mortality. Typical clinical symptoms include increased serum calcium levels, renal insufficiency, anemia, and bone lesions. With standard therapies, MM remains incurable; therefore, the development of new drugs or immune cell-based therapies is desirable. To advance the goal of finding a more effective treatment for MM, we aimed to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Similar observations have been reported by other groups examining different models of solid tumors and leukemia [21]. That a convenient, reliable and sensitive tracking of myeloma cells is indeed valuable with whole body imaging techniques in living animals has been demonstrated by various groups [22,23]. Bioluminescence and fluorescence imaging are widely used for determination of tumor load in preclinical in vivo studies.…”
Section: Discussionsupporting
confidence: 76%
“…Similar observations have been reported by other groups examining different models of solid tumors and leukemia [21]. That a convenient, reliable and sensitive tracking of myeloma cells is indeed valuable with whole body imaging techniques in living animals has been demonstrated by various groups [22,23]. Bioluminescence and fluorescence imaging are widely used for determination of tumor load in preclinical in vivo studies.…”
Section: Discussionsupporting
confidence: 76%
“…Next, we confirmed the ability of OSI-906 to overcome CAM-DR using another murine model, in which MOPC315.BM.Luc murine MM cells were injected intravenously into syngeneic BALB/c mice. Because MOPC315.BM.Luc cells engraft in the BM and interact with the BM microenvironment, this model accurately reflects human disease and is considered suitable for tropism analysis and drug testing (35)(36)(37). Using this model, we confirmed that CY was not able to inhibit the growth of MM cells engrafted in the BM, whereas OSI-906 alone significantly reduced tumor growth ( Figure 14, A and B).…”
Section: Therapeutic Effects Of the Igf-1r Inhibitor Osi-906 In Murinmentioning
confidence: 76%
“…To determine the acute effects of viral treatment on MRD, animals were killed 24 hours after the final treatment and tumor burden was directly measured using flowcytometry. 16 The results indicated that, in saline treated animals ( n = 10), CD138 hi /CD4 + MOPC-315 cells made up ~18% of the viable cells in the BM (Figure 3a). In contrast, all mice treated with MYXV ( n = 12) displayed a significantly reduced number of MOPC-315 cells in their BM (6.4%, P < 0.0001) indicating that viral treatment could acutely debulk MRD in vivo .…”
Section: Resultsmentioning
confidence: 94%